The Present state of communist internationalism - edited by Lawrence L. Whetten. (LexingtonBooks)
"The result of a workshop sponsored jointly by the Stiftung Wissenschaft und Politik at Ebenhausen, West Germany and the German Graduate Program of the University of Southern California"-- Acknowledgments.